An elderly patient's complete response to steroid therapy for collagenous gastritis. (August 2018) - Lim, Huei-Wen; Wong, Benny Yiu; Elkowitz, David; Sultan, Keith
An 85-year-old woman presented with 9.1 kg (20 lb) weight loss over 5 months and an acute onset crampy abdominal pain. Examination revealed a diffusely tender abdomen, with gastric wall thickening noted on CT scan. Upper endoscopy showed diffuse severe erythema and friability. Histologic examination with hematoxylin and eosin staining revealed collagenous gastritis characterized by active chronic inflammation with sub-epithelial collagen deposition and erosion. The patient was started on steroid therapy with rapid clinical improvement and tapered off over 2.5 months. At 6 months, the patient reported an improved appetite with resolution of her abdominal pain. Repeat endoscopy revealed a grossly normal stomach and normal mucosal biopsies. She remains without complaints 1 year later. Collagenous gastritis, rare in the elderly, is a histologic diagnosis characterized by the deposition of a sub-epithelial collagen band thicker than 10 µm with an inflammatory infiltrate. In all ages the mucosa typically appears nodular and erythematous, caused by an uneven inflammation in the surrounding depressed mucosa with atrophic changes. Specific therapy has not been well-established, and the prognosis and potential for endoscopic or histological resolution remains unclear. While anecdotal, the success of steroids may offer a reasonable starting point for treatment of similar cases.